Islamic Religious Education Based on Religious Intersubjectivity: Philosophical Perspectives and Phenomenology of Religion - Abdullah, M. Amin (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – This article discusses the idea of Islamic Religious Education based on religious intersubjectivity. Design/methods/approach – This paper presents the idea of Islamic Religious Education based on religious intersubjectivity with a philosophical perspective or approach and religious phenomenology. The philosophical approach is to delineate and discuss three varieties of new paradigm for religion, namely subjective, objective, and intersubjective belief. Meanwhile, the religious phenomenology approach is used to develop an